ESCLEROFILIZACION DEL PAISAJE MEDITERRÁNEO - Corcuera, Leyre; Morales, Fermín; Gil-Pelegrín, Eustaquio (IV Congreso Forestal Español, 2005)
La encina es una especie con una amplitud bioclimática muy grande ya que aparece en los bioclimas semiáridos, subhúmedos, húmedos y perhúmedos (sensu Ememberg) de la Península Ibérica. En las variantes frías del bioclima húmedo y perhúmedo Quercus ilex ballota compite con los robles deciduos, Quercus faginea y Quercus pyrenaica, ocupando las crestas de las montañas donde las condiciones geopedológicas no son adecuadas para el establecimiento de los robles deciduos. En la región mediterránea el cambio climático global reciente se ha reflejado en un incremento de la aridez y calidez, que tiende a acentuarse en el futuro. A largo plazo, esto podría afectar al funcionamiento y la estructura de los ecosistemas mediterráneos, provocando la sustitución de especies menos resistentes a la sequía o afectando a las poblaciones en localidades subóptimas o en el límite biogeográfico de su distribución. Se estudió el efecto de los dos estreses climáticos propuestos por Mitrakos: el estrés hídrico estival y el estrés por frío invernal en el crecimiento de la esclerófila perennifolia Quercus ilex ballota. Para ello se analizó el efecto de la sequía en el crecimiento primario y secundario de las especies concurrentes Quercus faginea y Quercus ilex ballota y el efecto de las bajas temperaturas y alta insolación en el aparato fotosintético de Quercus ilex ballota en un clima mediterráneo continental.
Keywords: cambio climático; cambios en el paisaje; carácter perennifolio/caducifolio; competencia interespecífica; Quercus spp

ESCLEROFILIZACION DEL PAISAJE MEDITERRÁNEO - Corcuera, Leyre; Morales, Fermín; Gil-Pelegrín, Eustaquio (IV Congreso Forestal Español, 2005)
La encina es una especie con una amplitud bioclimática muy grande ya que aparece en los bioclimas semiáridos, subhúmedos, húmedos y perhúmedos (sensu Ememberg) de la Península Ibérica. En las variantes frías del bioclima húmedo y perhúmedo Quercus ilex ballota compite con los robles deciduos, Quercus faginea y Quercus pyrenaica, ocupando las crestas de las montañas donde las condiciones geopedológicas no son adecuadas para el establecimiento de los robles deciduos. En la región mediterránea el cambio climático global reciente se ha reflejado en un incremento de la aridez y calidez, que tiende a acentuarse en el futuro. A largo plazo, esto podría afectar al funcionamiento y la estructura de los ecosistemas mediterráneos, provocando la sustitución de especies menos resistentes a la sequía o afectando a las poblaciones en localidades subóptimas o en el límite biogeográfico de su distribución. Se estudió el efecto de los dos estreses climáticos propuestos por Mitrakos: el estrés hídrico estival y el estrés por frío invernal en el crecimiento de la esclerófila perennifolia Quercus ilex ballota. Para ello se analizó el efecto de la sequía en el crecimiento primario y secundario de las especies concurrentes Quercus faginea y Quercus ilex ballota y el efecto de las bajas temperaturas y alta insolación en el aparato fotosintético de Quercus ilex ballota en un clima mediterráneo continental.
The following values have no corresponding Zotero field: periodical: IV Congreso Forestal Español pub-location: Zaragoza
Keywords: cambio climático; cambios en el paisaje; carácter perennifolio/caducifolio; competencia interespecífica; Quercus spp

Large daily variation in 13C-enrichment of leaf-respired CO2 in two Quercus forest canopies - Hymus, Graham J; MASEYK, KADMIEL; Valentini, Riccardo; Yakir, Dan (New Phytologist, 2005)
* • The use of the 13C : 12C isotopic ratio (δ13C) of leaf-respired CO2 to trace carbon fluxes in plants and ecosystems is limited by little information on temporal variations in δ13C of leaf dark-respired CO2 (δ13Cr) under field conditions. * • Here, we explored variability in δ13Cr and its relationship to key respiratory substrates from collections of leaf dark-respired CO2, carbohydrate extractions and gas exchange measurements over 24-h periods in two Quercus canopies. * • Throughout both canopies, δ13Cr became progressively 13C-enriched during the photoperiod, by up to 7, then 13C-depleted at night relative to the photoperiod. This cycle could not be reconciled with δ13C of soluble sugars (δ13Css), starch (δ13Cst), lipids (δ13Cl), cellulose (δ13Cc) or with calculated photosynthetic discrimination (Δ). However, photoperiod progressive enrichment in δ13Cr was correlated with cumulative carbon assimilation (r2 = 0.91). * • We concluded that there is considerable short-term variation in δ13Cr in forest canopies, that it is consistent with current hypotheses for 13C fractionation during leaf respiration, that leaf carbohydrates cannot be used as surrogates for δ13Cr, and that diel changes in leaf carbohydrate status could be used to predict changes in δ13Cr empirically.
Keywords: carbon isotope ratio; dark respiration; forest canopies; fractionation; Quercus spp

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, a; Mediavilla, S (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp

Decline in photosynthetic nitrogen use efficiency with leaf age and nitrogen resorption as determinants of leaf life span - Escudero, A.; Mediavilla, S. (Journal of Ecology, 2003)
* 1Cost-benefit models predict that leaf life span depends on its initial photosynthetic rate and construction cost and on the rate of decline in photosynthesis with age. Leaf gas exchange rates and N contents were measured in nine woody evergreen Mediterranean species with different leaf life spans to determine the effects of leaf ageing on photosynthetic N use efficiency (PNUE). N costs of leaf construction were assumed to be in part dependent on N resorption from senescing leaves. * 2Leaf ageing had significant negative effects on photosynthetic rates per unit leaf area. As N content per unit leaf area did not decline until the end of leaf life, PNUE also decreased with age. PNUE generally declined faster in species with a shorter leaf life span. There were no significant interspecific differences in maximum CO2 assimilation rates per unit leaf area and in N resorption that could be related to differences in leaf life span. * 3As PNUE decreases with leaf age, shedding of the older leaves and retranslocation of N to the current year's leaf biomass would result in an increase in the mean instantaneous efficiency of use of the N retranslocated. However, total CO2 assimilation can be improved by such shedding only when the increase in the efficiency of use of the remobilized N compensates for the remaining N lost in the shed leaves. * 4The photosynthesis of the old leaf cohorts exceeded the increase in photosynthesis that would be obtained from the N retranslocated to the younger leaves, given the observed efficiencies of N resorption. The retention of old leaves thus resulted in a higher whole-canopy CO2 assimilation, despite their low PNUE.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: leaf life span; N resorption; photosynthetic nitrogen use efficiency; Pinus spp.; Quercus spp